Numerical predicction and infographics in the environmental recovery of marble quarries - Alarcón Martínez, Virginia; Tejero Claver, Blanca; Garrido Sáez, Neus (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
In the Spanish geography, there are a large number of abandoned marble quarries in which no restoration plan has been carried out, with the consequent environmental degradation that this entails. This study is based on the use of infographics to assess the environmental recovery of these abandoned marble quarries in a quick and easy way. A linear regression analysis is also carried out to study the soil type of the samples and to make numerical predictions about some of their physicochemical characteristics. The conclusions show the great possibilities offered by the addition of different amendments from an environmental and economic point of view.